Elemental Contamination in Various Species of Birds from Select States in India - Venkatasalam, Kirubhanandhini; Subramanian, Muralidharan; Kittusamy, Ganesan; Jadhav, Shashikant Shivaji (Asian Journal of Engineering and Applied Technology, 2019)
With the aim, to assess the magnitude of elemental contamination in birds in select states in India, samples of bird tissues were analyzed for copper (Cu), lead (Pb), cadmium (Cd) and chromium (Cr), with Atomic Absorption Spectrophotometer. Elements were detected in all the tissues and significant differences were noted in their concentrations among the species and tissues (P>0.05). Out of the 10 species analyzed, Bar – headed Goose and Red – wattled Lapwing accumulated the highest and Eurasian Collared – dove the lowest concentration of all the elements analyzed. Of all the tissues, kidney accumulated the maximum concentration of Pb (11.77 μg/g), Cd (17.06 μg/g) and Cr (16.08 μg/g). Apart from the organs studied, gut content also had notable levels of elements, which indicated the present contamination status of the environment. Nonetheless, the levels of most of the elements measured in the present study were considered non-toxic.